Myosin X regulates neuronal radial migration through interacting with N-cadherin - Lai, Mingming; Guo, Ye; Ma, Jun; Yu, Huali; Zhao, Dongdong; Fan, Wenqiang; Ju, Xingda; Sheikh, Muhammad A.; Malik, Yousra S.; Xiong, Wencheng; Guo, Weixiang; Zhu, Xiaojuan (Frontiers in Cellular Neuroscience, 2015)
Proper brain function depends on correct neuronal migration during development, which is known to be regulated by cytoskeletal dynamics and cell-cell adhesion. Myosin X (Myo10), an uncharacteristic member of the myosin family, is an important regulator of cytoskeleton that modulates cell motilities in many different cellular contexts. We previously reported that Myo10 was required for neuronal migration in the developing cerebral cortex, but the underlying mechanism was still largely unknown. Here, we found that knockdown of Myo10 expression disturbed the adherence of migrating neurons to radial glial fibers through abolishing surface N-cadherin expression, thereby impaired neuronal migration in the developmental cortex. Next, we found Myo10 interacted with N-cadherin cellular domain through its FERM domain. Furthermore, we found knockdown of Myo10 disrupted N-cadherin subcellular distribution and led to localization of N-cadherin into Golgi apparatus and endosomal sorting vesicle. Taking together, these results reveal a novel mechanism of Myo10 interacting with N-cadherin and regulating its cell-surface expression, which is required for neuronal adhesion and migration.